2015
DOI: 10.1093/cid/civ596
|View full text |Cite
|
Sign up to set email alerts
|

Community Perspectives Associated With the African PsA-TT (MenAfriVac) Vaccine Trials

Abstract: Background. The Meningitis Vaccine Project (MVP) was established to address epidemic meningitis as a public health problem in sub-Saharan Africa and, to that end, worked to develop a group A meningococcal conjugate vaccine, PsA-TT.Methods. Experiences in 4 clinical trial sites are described. Culturally sensitive collaborative strategies were adopted to manage acceptable communication methods, peculiarities with the consent process, participant medical issues, community care, and death.Results. The clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The major joint achievement of this process was to engender an atmosphere of trust that enabled the study to proceed and the community to feel properly involved. 3 In a multi-country trial of a Group A meningococcal conju-40 gate vaccine, 4 investigators found it useful to include local journalists in the liaison team on the ground. They also learned the importance of including husbands and male household heads in preliminary discussions about the trial.…”
Section: Q3mentioning
confidence: 99%
“…The major joint achievement of this process was to engender an atmosphere of trust that enabled the study to proceed and the community to feel properly involved. 3 In a multi-country trial of a Group A meningococcal conju-40 gate vaccine, 4 investigators found it useful to include local journalists in the liaison team on the ground. They also learned the importance of including husbands and male household heads in preliminary discussions about the trial.…”
Section: Q3mentioning
confidence: 99%
“…While bioethics has been engaged in political issues from the very start, the ethics of research with human subjects has found its own path in dealing with politics and cultural issues. Especially the procedure of obtaining informed consent has been adapted to various political and cultural circumstances in different places of the world (Idoko et al 2015). Community consent prior to or concomitant with individual consent has become a practice in the last 10 to 15 years (Embleton et al 2015).…”
Section: Bioethics Ethics Of Human Research and Politicsmentioning
confidence: 99%
“…The success of any clinical study is largely dependent on community and participant support. The importance of community involvement in international clinical trials has become increasingly recognized [ 5 – 8 ].…”
Section: Community Permissionmentioning
confidence: 99%
“…Initial community meetings prepared by the study investigators in collaboration with partners established a format for dialogue between the research team and the population, which was maintained throughout the study. The research staff, investigators, and fieldworkers, who often belonged to these communities, played a critical role in keeping the communities engaged [ 5 ].…”
Section: Community Permissionmentioning
confidence: 99%
See 1 more Smart Citation